Diadromous Fish Enhancement and Restoration: 2004 Annual Performance Report - Gephard, S; Wildman, T; Williams, B; Ellis, D (ScholarWorks@UMass Amherst, 2005)
From executive summary: The purpose of this project is to restore and enhance diadromous fish runs to the streams of Connecticut through the provision of effective fish passage and the reintroduction of fish into selected watercourses. The scope of this project was expanded in 2003 to include jobs for American eel and sea-run trout. Other jobs were also re-organized. The goals of this project are: (1) To restore Atlantic salmon to three tributaries of the Connecticut River in Connecticut. (2) To restore and enhance runs of American shad in ten streams in Connecticut. (3) To restore and enhance runs of river herring in 30 streams in Connecticut. (4) To restore and enhance runs of American eel in 20 streams in Connecticut. (5) To develop and enhance runs of sea-run trout in eight streams in Connecticut. (6) To provide effective fish passage at 30 existing fish passage facilities. (7) To provide effective fish passage at 30 existing barriers to fish migration. (8) To expand public knowledge of the success of diadromous fish restoration and its importance to the health of Connecticut's ecological resources.